The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1002/1096-9101(2001)28:1<1::aid-lsm1009>3.3.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Laser‐mediated cartilage reshaping with feedback‐controlled cryogen spray cooling: Biophysical properties and viability

Abstract: Background and Objective:Recent studies have indicated that chondrocyte viability decreases with prolonged or repeated laser irradiation. To optimize laser-mediated cartilage reshaping, the heating process must be finely controlled. In this study, we use high-power Nd:YAG laser irradiation ( ‫ס‬ 1.32 m) combined with cryogen spray cooling (CSC) in an attempt to reshape porcine septal cartilage while enhancing chondrocyte viability. Study Design/Materials and Methods: Chondrocyte viability was determined after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…Instead, these findings suggest that in order to produce clinically relevant shape change in cartilage tissue using the Nd:YAG, significant cellular damage will occur within the region of energy deposition and heat conduction [2]. The success of LCR procedures reported in both animal studies [2,12] and clinical trials [11] likely depends upon spatially selective heating where reshaping may result from deposition of energy into well-defined layers within a specimen or graft leading to mechanical relaxation of this region alone [8]. Cartilage tissue beneath this level likely undergoes little temperature elevation and thus remains viable and may participate in the remodeling process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, these findings suggest that in order to produce clinically relevant shape change in cartilage tissue using the Nd:YAG, significant cellular damage will occur within the region of energy deposition and heat conduction [2]. The success of LCR procedures reported in both animal studies [2,12] and clinical trials [11] likely depends upon spatially selective heating where reshaping may result from deposition of energy into well-defined layers within a specimen or graft leading to mechanical relaxation of this region alone [8]. Cartilage tissue beneath this level likely undergoes little temperature elevation and thus remains viable and may participate in the remodeling process.…”
Section: Discussionmentioning
confidence: 99%
“…LCR is a potential improvement over classic surgical techniques that rely on incisions, morselization, or suturing to balance the elastic forces in cartilage that resist deformation [2]. While some animal [11,12] and human studies [1,2,11] have demonstrated promising results, the clinical relevance of LCR still depends on its ability to minimize and/or limit thermal injury in irradiated regions [2,13]. In order to better understand the safety of LCR, both shape change and resultant tissue viability must be determined as a function of laser dosimetry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, specimens were irradiated for 15 seconds with a Nd:YAG laser (l 1.32 mm, 50-Hz PPR, 5W, 6-mm spot diameter, New Star Lasers, Auburn, CA). These laser parameters are similar to those used in previous investigations by our group [13,16] . The laser beam was directed at the center of the specimen along the center of the bend specimen ( Fig.…”
Section: Laser Irradiation and Reshapingmentioning
confidence: 99%
“…The alteration in internal stress during laser irradiation results in accelerated stress relaxation and represents a fundamental biophysical change that results in cartilage reshaping [18,23,24]. Preliminary studies using diffuse light scattering and calorimetric measurements have identified changes in cartilage tissue, thermal and optical properties that are consistent with this phase transformation hypothesis [11][12][13]15,19,20,[25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%